ANALYSIS AND VALIDATION OF DETECTION METHOD FOR ETHYLENE AND DIETHYLENE GLYCOL CONTAMINANTS IN SYRUP USING GCMS (GAS CHROMATOGRAPHY-MASS SPECTROMETER) - Supandi, Supandi; Mustafidah, Mabrurotul; Yaenap, Siti; Rumblat, Walid (Universitas Muhammadiyah Magelang, 2025)
Ethylene glycol (EG) and diethylene glycol (DEG) are hazardous compounds if ingested by the human body. Testing conducted by the Indonesian National Agency of Drug and Food Control (BPM) identified contamination of EG and DEG in glycerin and propylene glycol, which are utilized as solubility enhancers in syrup-based pharmaceuticals. This study aims to analyze EG and DEG contamination in children’s syrup drug samples using a Gas Chromatography-Mass Spectrometry (GC-MS) instrument. This study presents an analytical method for detecting EG and DEG contamination. Based on BPOM regulations governing the control a determination of EG and DEG. Several syrup drug samples, which are listed in the BPOM drug withdrawal list under Number HM.01.1.2.11.22.240, were each weighed at 5 grams, transferred into a 50 mL volumetric flask, 30 mL of methanol was added, and the mixture was sonicated for 5 minutes. Subsequently, solvent was added up to the calibration mark. Five out of eight samples were found to contain EG and DEG at concentrations of less than 0.1%. Validation of the GCMS method for EG and DEG compounds yielded accuracy values with recovery rates between 98% and 101%. The acquisition test results produced a relative standard deviation (RSD) value of 0.87. The linearity test showed a correlation coefficient (r) of 0.955. The limit of detection (LOD) for EG was 0.26 ng/mg, and for DEG it was 0.51 ng/mg. The limit of quantification (LOQ) for EG was 0.86 ng/mg, and for DEG it was 1.69 ng/mg. This validation indicates that the analytical method exhibits high accuracy and sensitivity.